GSDMD contributes to myocardial reperfusion injury by regulating pyroptosis - Ye, Xiaomiao; Zhang, Peng; Zhang, Yuting; Luan, Jingyun; Xu, Caili; Wu, Zhengyu; Ju, Dianwen; Hu, Wei (Frontiers in Immunology, 2022)
Background: Gasdermin D (GSDMD) plays an essential role in the pathway of pyroptosis. However, whether GSDMD participates in myocardial ischaemia/reperfusion injury (MI/RI) remains poorly understood. Methods: Serum levels of GSDMD in ST-segment elevation myocardial infarction (STEMI) patients were measured by ELISA. The expression of GSDMD and GSDMD N-terminal (GSDMD-NT) in vivo and in vitro was assessed by western blotting and immunofluorescence staining. GSDMD-/- mice and wild type (WT) mice were induced MI/RI, followed by cardiac ultrasound and histological analysis. Results: Clinically, patients suffering from STEMI after percutaneous coronary intervention (PCI) exhibited higher levels of GSDMD and IL-18 than that in the controls. In vitro, the cleavage of GSDMD was significantly upregulated in macrophages exposed to hypoxia/reoxygenation or H2O2. In vivo, the levels of GSDMD and GSDMD-NT increased notably after MI/RI, especially in macrophages infiltrating in the infarct area. Moreover, GSDMD-/- mice showed reduced infarct size (25.45±3.07% versus 36.47±3.72%), improved left ventricular ejection fraction (37.71±1.81% versus 29.44±2.28%) and left ventricular fractional shorting (18.01±0.97% versus 13.62±1.15%) as well as attenuated pathological damage after I/R injury, along with reduced levels of proinflammatory cytokines and decreased infiltration of neutrophils. Conclusions: Our study revealed that GSDMD deficiency significantly alleviated the inflammatory response by regulating pyroptosis, reducing the infarct size and preserving cardiac function after MI/RI, thus providing a potential strategy for the treatment of myocardial reperfusion injury. Keywords: gasdermin D, myocardial reperfusion injury, pyroptosis, interleukin 1β, interleukin 18